Practical Parallel of Autonomous Unmanned Aerial Vehicle by Mission Planner - Chairat Suparnunt; Chon Boonvongsobhon; Farhaad Eounes Baig; Prachaya Leelalerthpat; Warunyu Hematulin; Tanatthep Jarawan; Patcharin Kamsing (IGARSS 2022 - 2022 IEEE International Geoscience and Remote Sensing Symposium, 2022)
Satellite imaging has always been a challenging task and at the current time being there are very few alternatives for capturing vertical images of Earth's vast landscape. Aerial photography by using multiple unmanned aerial vehicles (UAV) might be one of the solutions. This research aims to study, improve and demonstrate autonomy for UAVs by using specialized software and apparatus. The mission can be utilized to allow the UAVs to fly sequentially in the same pathway without colliding and creating the highest amount of coverage, which it is important for some remote sensing applications. Certain benefits can be obtained from using UAV rather than satellite imaging such as lower cost of overall equipment than a space satellite and higher resolution pictures due to flexibility in altitude operations. The results of implement the autonomous UAV has compare between path of actual flight and the setting way-points and it express exceptional results by presenting less of Root Mean Square Error.
Keywords: Robotic Path Planning Algorithms; Robotics and Sensor-Based Localization; Optimization and Search Problems